Psychometric validation of the German version of the somatic symptom disorder-B criteria scale (SSD-12) in a primary care population with depression and anxiety: a COSMIN-guided analysis - Eickels, Deborah van; Henning, Klara; Wensing, Michel; Friederich, Hans-Christoph; Haun, Markus W. (General hospital psychiatry, 2025)
Objective - Somatic Symptom Disorder (SSD) is common and often underdiagnosed in primary care, especially in patients with depression and anxiety. The SSD-12 is a self-report questionnaire assessing psychological features of SSD. This study aimed to validate the SSD-12 longitudinally in a primary care sample with depressive and/or anxiety symptoms, following COSMIN guidelines. - Methods - We conducted a secondary analysis of the PROVIDE-C trial, including 365 adults with moderate depressive and/or anxiety symptoms. Psychometric evaluation of the SSD-12 used data from three time points (baseline, 6, and 12 months). Factorial validity was assessed via confirmatory factor analysis (CFA) comparing unidimensional and three-factor models. Measurement invariance was examined across gender, age, chronic illness, and study arms using multi-group and longitudinal CFA. Additional analyses included internal consistency (McDonald's Omega), test-retest reliability (ICC), measurement error (SEM, SDC), convergent validity (correlations with PHQ-9, GAD-7, RAS-G, SF-12, EQ-5D), and responsiveness (correlations of SSD-12 change scores with PHQ-ADS change). - Results - CFA supported a three-factor structure (cognitive, affective, behavioral) at all time points. Measurement invariance was confirmed across subgroups and longitudinally. The SSD-12 showed high internal consistency, adequate test-retest reliability, and good responsiveness. Construct validity showed moderate positive correlations with anxiety, and small positive correlations with depression. - Conclusion - The SSD-12 exhibits strong psychometric properties in psychologically burdened primary care patients and is suitable for screening and monitoring somatic symptom burden in both cross-sectional and longitudinal examinations. Further research should refine thresholds for clinically meaningful change and cut-off points across diverse patient groups to enhance clinical interpretability. Trial registration: ClinicalTrials.gov NCT04316572.
Online verfügbar 4 September 2025, Version des Artikels 11 September 2025
Gesehen am 15.01.2026